2004
DOI: 10.1038/sj.sc.3101674
|View full text |Cite
|
Sign up to set email alerts
|

Increased production of reactive oxygen species contributes to motor neuron death in a compression mouse model of spinal cord injury

Abstract: Study design: Experimental laboratory investigation of the role and pathways of reactive oxygen species (ROS)-mediated motor neuron cell death in a mouse model of compression spinal cord injury. Objectives: To analyze ROS-mediated oxidative stress propagation and signal transduction leading to motor neuron apoptosis induced by compression spinal cord injury. Setting: University of Louisville Health Science Center. Methods: Adult C57BL/6J mice and transgenic mice overexpressing SOD1 were severely lesioned at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(111 citation statements)
references
References 31 publications
4
100
0
3
Order By: Relevance
“…The experimental model for acute mouse compression SCI was essentially similar to that previously described by Farooque [37] but with minor modifications [38]. Briefly, animals were deeply anesthetized with pentobarbital in a dose of 20 mg/kg body weight by i.p.…”
Section: Compression Scimentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental model for acute mouse compression SCI was essentially similar to that previously described by Farooque [37] but with minor modifications [38]. Briefly, animals were deeply anesthetized with pentobarbital in a dose of 20 mg/kg body weight by i.p.…”
Section: Compression Scimentioning
confidence: 99%
“…The acute compression injury mouse model was selected to analyze the early response of NPCs to SCI according to a similar procedure described by Farooque [37] but with minor modifications [38]. Mild (15 g of weight for 5 minutes), moderate (20 g of weight for 5 minutes), and severe (30 g of weight for 5 minutes) lesion conditions were applied to generate different degrees of SCI.…”
Section: Tissue Damage and Neurological Dysfunction In Acute Compressmentioning
confidence: 99%
“…Because previous studies have demonstrated that hypoxic condition or mechanical compression stimulates ROS generation, we first examined whether the intracellular ROS level is increased by mechanical compression or hypoxic treatment in human PDLFs cultured in vitro (Chandel et al, 1998;Xu et al, 2005). The levels of intracellular ROS were significantly increased when PDLFs were exposed to a mechanical compression of 0.5 to 3 g/cm 2 for 4 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that mechanical compression of cartilage or the spinal nerve increases the recruitment of inflammatory cells to these tissues, resulting in ROS production, inflammatory responses and subsequent tissue damage (Burkhardt et al, 1986;Xu et al, 2005). However, it is not clear whether the mechanical compression of cells induces ROS production in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation